Bioprocesses in the Era of Artificial Intelligence - Luis Miguel Serrano-Bermúdez (Revista Colombiana de Biotecnología)
Bioprocesses are a branch of biotechnology focused on the use of bioinputs (cells or their derivatives) and technologies for the production and purification of commercially relevant bioproducts from raw materials. These bioproducts can be classified into commodities, such as probiotics or biofuels, and specialties, such as monoclonal antibodies or gene therapies. On the other hand, scientific and technological advances have driven the development of artificial intelligence (AI), a disruptive tool that is part of the Fourth Industrial Revolution and is transforming multiple sectors, even integrating into daily life. In this context, AI also has the potential to be integrated into bioprocesses to improve key indicators related to the bioproduct and raw materials, such as production, productivity, yield, and conversion.